2016
DOI: 10.1136/bmjopen-2016-011993
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of injuries sustained in motor vehicle crashes: systematic review and meta-analysis

Abstract: ObjectiveThe aim of this meta-analysis was to determine the psychological impact associated with motor vehicle crash (MVC)-related physical injuries.DesignSystematic review and meta-analysis.Data sourcesMultiple search engines included MEDLINE (via OVID), PsycINFO and Embase, and studies were sourced from scientific journals, conference papers and doctoral theses.Study selectionA high-yield search strategy was employed. Terms like ‘psychological distress’, ‘depression’, ‘PTSD’ and ‘motor vehicle accident’ were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
101
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 74 publications
2
101
2
1
Order By: Relevance
“…It has been shown that an ongoing compensation process affects the claimants' quality of life negatively, both physically and mentally [13,22] and that a prolonged time to claim closure is a negative prognostic parameter [13,23]. Indirectly, this could be correlated with being an experience of non-recovery after the index trauma [24] and support the "compensation theory" [14]. In this study, no difference in outcome between the participants with open and closed cases could be detected.…”
Section: Discussionmentioning
confidence: 47%
“…It has been shown that an ongoing compensation process affects the claimants' quality of life negatively, both physically and mentally [13,22] and that a prolonged time to claim closure is a negative prognostic parameter [13,23]. Indirectly, this could be correlated with being an experience of non-recovery after the index trauma [24] and support the "compensation theory" [14]. In this study, no difference in outcome between the participants with open and closed cases could be detected.…”
Section: Discussionmentioning
confidence: 47%
“…Psychosocial factors are important determinants of outcome after work injury [20, 21]. The biopsychosocial approach has been widely advocated in medicine, but, based on communication with insurance companies, the biopsychosocial model does not seem to have been fully adopted into the compensation systems as yet.…”
Section: Discussionmentioning
confidence: 99%
“…Most reported transport accidents result in minor injuries (75%), mostly musculoskeletal and/or soft tissue injuries . The injury itself, regardless of severity, may lead to permanent mental and physical impairments and disabilities . Even though minor injuries comprise approximately 75% of all road transport injuries, poor physical and mental health outcomes in this group have received little attention .…”
Section: Introductionmentioning
confidence: 99%
“…Even though minor injuries comprise approximately 75% of all road transport injuries, poor physical and mental health outcomes in this group have received little attention . Among participants with minor injuries, there are individuals at high risk of substantial poor recovery and on‐going disability . Hence, permanent or temporary disabilities arising from minor injuries pose an on‐going problem for the compensation and health‐care system .…”
Section: Introductionmentioning
confidence: 99%